Improving Performance Through Job Satisfaction - Nurseha, Haikal; Farida Ferine, Kiki (PT. Multidisciplinary Press Indonesia, 2024)
This research aims to see the influence of mutation and work environment on employee performance with job satisfaction as an intervening variable. With quantitative as the type of research, primary as the source and data collection is used by distributing questionnaires and Likert scales, the research population is 60 employees and the sample is also 60 employees because all the sampling techniques used are saturated sampling techniques. The results of this research are as follows: Job Satisfaction has a positive and significant effect on Employee Performance with an original sample value of 0.443 and ap value of 0.000. Work Environment has a positive and significant effect on Job Satisfaction with an original sample value of 0.461 and ap value of 0.001. The work environment has a positive and significant effect on employee performance with an original sample value of 0.275 and ap value of 0.021. Mutations have a positive and significant effect on Job Satisfaction with a value of 0.443 and a value of 0.002. Mutations have a positive and significant effect on employee performance with an original sample value of 0.239 and ap value of 0.032. The work environment influences employee performance indirectly through job satisfaction positively and significantly with an original sample value of 0.204 and ap value of 0.014. Mutations influence employee performance indirectly through job satisfaction with an original sample value of 0.196 and ap value of 0.010.